Sustainability after COVID-19: pillars for a just transition - Morrissey, John; Heidkamp, Patrick (Environmental Sustainability, 2022)
The vulnerability of the global economy has been starkly exposed by the COVID-19 pandemic. Longer term thinking and new approaches to development and prosperity are urgently required. In this paper, we forward a series of principles on which economic and development policy for the post-COVID era should be developed. These are outlined as five ‘pillars’ from which to rebuild the global economy, based on principles of a shared sustainable prosperity. These pillars are: (I) an ecological prosperity; (II) a decarbonized economy; (III) a shared cost burden; (IV) a governance new deal; (V) a just resilience. In outlining the ‘5 pillars’ we explicitly recognize that sustainability cannot simply be a ‘green’, or environmental concern. Social and economic dimensions of sustainability are key for societal stability and continuity. This is made ever starker in the context of the fundamental economic and societal restructuring forced by the disruption of the COVID-19 pandemic. In this regard, the pillars represent a triple bottom line framing of sustainability, of mutually supportive domains of economic, social and environmental well-being. The five pillars are informed by principles of distributive and procedural justice, recognizing the importance and advantages of real community engagement and empowerment and giving due respect and deference to the ecological carrying capacity of our fragile planet. We argue that the post-COVID-19 re-build represents a once-in-a generation opportunity to markedly shift developed trajectories to more sustainable pathways, to rebalance the domains of sustainability, and in the process, to address longer-term crises including those of climate and biodiversity loss.
Keywords: COVID-19; Climate crisis; Prosperity; Resilience; Social justice; Sustainability; dept.egm; peer-reviewed

Introduction - Morrissey, John; Heidkamp, C. Patrick; Garland, Michaela; Krak, Louie (Demanding Sustainability: Pillars to (Re-)Build a Shared Prosperity, 2022)
This chapter introduces the 5 ‘pillars’ through which to (re-)build a shared sustainable prosperity. The five pillars aim to provide a framework through which policymakers, decision-makers, politicians, community groups and the corporate sphere might begin to consider, map out and plan for just transitions in their domains. The theoretical framing combines socio-technical transitions, social justice and just transitions perspectives; the novelty of our proposed approach here is the further inclusion of resilience perspectives, to account for the shifting relations between sustainability and resilience. Our understanding of sustainability aligns with a ‘strong sustainability’ perspective, whereby ecological limits represent ‘hard’ limits to development, limits which need to be acknowledged and respected.
Keywords: Just transitions; Pillars; Social justice; Socio-technical transitions; Strong sustainability; Sustainable prosperity; dept.egm

Demanding Sustainability: Pillars to (Re-)Build a Shared Prosperity - Morrissey, John; Heidkamp, C. Patrick (Springer International Publishing, 2022)
Keywords: Climate Crisis; Covid; Covid-19; decarbonized economy; dept.egm; ecological prosperity; global economy; just resilience; resilience; social justice; sustainable governance; sustainable prosperity

Ch. 1 - Blue Economy: People and Regions in Transitions - Heidkamp, C.P.; Morrissey, J.; Germond-Duret, C.; Rourke, M. (Blue Economy: People and Regions in Transitions, 2022)
Keywords: dept.egm

Effective Stakeholder Engagement in Coastal Rransitions: Floating away from the DAD Approach towards the MOM Method - Kelly, Miriah; Axon, Stephen (Blue Economy: People and Regions in Transitions, 2022)
Emerging literature on coastal transitions in the face of the climate crisis establishes a need for identifying appropriate stakeholder engagement processes for
Num Pages: 12
Keywords: dept.egm

Strengthening Industry and Academic Links Through Transdisciplinary Action Research: An Introspective Reflection of a Collaborative Water Quality, Biodiversity, and Aquaculture Initiative - Brideau, Lauren; Cross, Emma L.; Govindarajan, Annette F.; Martino, Dan; Martino, Greg; Holland, Miranda; Triay, Gabriela; Heidkamp, C. Patrick (Blue Economy: People and Regions in Transitions, 2022)
As anthropogenic impacts such as climate change ensue, coastal regions become increasingly threatened. Transdisciplinary action research (TAR) emerged as a
Num Pages: 14
Keywords: SCSU-student; dept.egm

Community Acceptance of Blue Energy: Identifying Future Research Trajectories for Understanding “Place-Technology-Fit” Perceptions - Axon, Stephen (Blue Economy: People and Regions in Transitions, 2022)
Offshore renewable, or Blue Energy, installations are a crucial component of many countries’ energy policies and pathways towards a sustainable low-carbon
Num Pages: 14
Keywords: dept.egm

Blue Economy: People and Regions in Transitions - Heidkamp, C. Patrick; Morrissey, John Edward; Duret, Celine Germond (Routledge, 2022)
This book presents state-of-the-art perspectives on the Blue Economy. It applies important geographical and sustainability transitions perspectives and
Keywords: dept.egm

The Evolution of Blue Carbon: Exploring the Burgeoning Role of Macroalgae in Carbon and Nitrogen Sequestration - Krak, Louie; Heidkamp, C. Patrick (Blue Economy: People and Regions in Transitions, 2022)
The recent attention on Blue Carbon (BC) signals its importance in the burgeoning Blue Economy discourse. BC has traditionally referred to carbon that is
Num Pages: 32
Keywords: dept.egm

(In)justice and the blue economy - Germond-Duret, Celine; Heidkamp, C. Patrick; Morrissey, John (The Geographical Journal, 2022)
While the ocean space has long been ignored by social sciences, the past 15 years have witnessed an increased interest in the marine environment by scholars in Human Geography. The academic literature on the blue economy, almost non-existent a few years ago, is now burgeoning. The academic debate has offered some critical assessment of blue economy initiatives, but more needs to be done to address the true place of environmental protection within a blue economy, and to put people at the centre of concerns and analyses. Of particular concern, is the ambiguity of the blue economy concept and the confusion over its social and environmental sustainability, which can ultimately result in harmful practices. An important question is then how should social scientists in general and geographers, specifically, engage with these debates, and in particular how should the potential human and social costs of the blue economy be investigated and addressed while assuring justice and fairness? The papers presented here share the vision that environmental sustainability, justice and equality should be at the heart of the blue economy; not just conceptually, but practically too. The papers pursue efforts to identify blue economy risks and the mechanisms through which they occur; assess the place of inclusion and participation in a sustainable blue economy; define what blue economy policies should include to drive just and sustainable practices; and identify where the dominant understandings of the blue economy and its priorities are coming from. In other words, they put considerations of justice and broader cultural structures at the centre of their concerns and analysis. They also highlight the need to bypass geographical boundaries and gain insights from other disciplines and methodologies to grasp such an encompassing concept, and foster not just a blue economy with social justice, but a blue economy for social justice.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/geoj.12483
Keywords: blue economy; communities; dept.egm; justice; peer-reviewed; sustainability

Geographical considerations for capturing value in the U.S. sugar kelp (Saccharina latissima) industry - Heidkamp, C. Patrick; Krak, Louie Vincent; Kelly, Miriah M. Russo; Yarish, Charles (Marine Policy, 2022)
The United States’ seaweed industry is worth over $300 million annually thanks in part to the rising popularity of seaweed-based products. Seaweed has myriad uses and great potential for novel product innovation and development while also providing numerous environmental benefits including carbon and nitrogen sequestration and other crucial ecosystem services . One of the most promising and prevalent species under domestic cultivation is Saccharina latissma. Also known as sugar kelp, this abundantly grown cold-water species dominates the edible seaweed market in the United States . This paper provides an in-depth geographical analysis of the current state of the U.S. sugar kelp industry, comparing regional market differences and opportunities for growth in Maine, Alaska, and Connecticut. Data was collected from the 2020 National Sea Grant Seaweed Symposium (https://seaweedhub.org/symposium/) and through a series of semi-structured interviews with key industry participants, yielding insights into the challenges that seaweed stakeholders face across the country. Proposed solutions for increasing the profitability of sugar kelp are explored and include market differentiation through regional origin labels, eco-labels, and quality labels.
5 citations (Crossref) [2023-10-31]
Keywords: Eco-labels; Ecosystem services; Market differentiation; Origin labels; Quality labels; Seaweed; Sugar kelp; dept.egm; peer-reviewed

Red nectar presentation and characterization of the breeding system of an Andean nightshade - Mione, Thomas; Cotton, Anna C.; Leiva González, Segundo; Yacher, Leon I. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2022)
Flowers of Jaltomata weigendiana (Solanaceae) secrete red nectar that is visible through the partially translucent corolla. We report the pattern of nectar presentation during the sexual phases of the flower and characterize the breeding system. Comparison of flower sets experiencing daily removal starting Day 1 with flowers that accumulated nectar for one or two days prior to daily removal revealed no discernible effect on the life-of-the-flower nectar production, sugar production and floral longevity. Flowers produce about the same cumulative volume of nectar during the two sexual phases. However, cumulative nectar sugar production is about 4 times higher during the male phase. Nectar standing crop ranged from 4–26.6 µl for Day 1 flowers and 0–8.7 µl for flowers from which nectar was removed the previous day. With daily removal of nectar, 21 of 40 flowers contained no nectar during the last day of the flower’s life. All unmanipulated flowers developed fruits (autonomous self-pollination). However, manual self-pollinations and manual cross-pollinations resulted in fruits that weighed significantly more and had significantly more seeds than fruits produced by autonomous self-pollination. Protogyny and herkogamy promote cross-pollination, but delayed autonomous selfing at the end of the flower’s life ensures seed set if pollinator-mediated pollination fails.
2 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/11263504.2022.2100499
Keywords: Autonomous self-pollination; Jaltomata; Solanaceae; colored nectar. edible fruit; dept.egm; floral longevity; peer-reviewed; protogyny; red nectar

Beyond stakeholder engagement in the coastal zone: Toward a systems integration approach to support just transformation of the blue economy - Kelly, Miriah M. Russo (The Geographical Journal, 2022)
Transformation has become a prevailing and desirable concept in blue economy literature. In parallel, researchers have been considering ways to effectively engage stakeholders to support just transformational agendas. Globally, coastal communities are already being affected by the inevitable impacts of climate change and changes to the blue economy. These pressures present complex contexts for coastal zone stakeholder engagement. In this paper, I argue that taking a systems integration approach to interacting with stakeholders is needed to support just transformational change. Assessing stakeholder systems and their relationship to coastal resources is imperative for understanding dynamics that may promote or hinder just transformation. Taking an adaptive management approach to working alongside stakeholders through transitional processes, thus building capacity, is needed to generate momentum toward just transformational change. Lastly, I explain how applications of the subsidiarity principle in integrating stakeholder systems can support a just transformational process and can inform more durable transformational outcomes.
1 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/geoj.12452
Keywords: blue economy; coastal; dept.egm; just transition; peer-reviewed; stakeholder; systems integration; theoretical model

Tools for Healthy Living: Lessons Learned About Program Efficacy, Youth Knowledge, and Youth Engagement - Gray, Sharon; Cushman, Jennifer; Kelly, Miriah; Gaudio, Mary Margaret; Gubbins, E. Jean (The Journal of Extension, 2022)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm; peer-reviewed

The US Blue New Deal: What does it mean for just transitions, sustainability, and resilience of the blue economy? - Axon, S.; Bertana, A.; Graziano, M.; Cross, E.; Smith, A.; Axon, K.; Wakefield, A. (Geographical Journal, 2022)
The ocean and coasts are largely absent from the “Green New Deal” proposal. In response to the limited attention paid to the sustainability and equitable governance approaches of the blue economy, a US “Blue New Deal” has been proposed aiming to protect the health of the ocean and support coastal communities' adaptation to climate change. The Blue New Deal emerged as a central policy proposal from 2020 Democratic presidential candidate Elizabeth Warren to enhance the role of the blue economy while simultaneously addressing the climate crisis. Through a just transitions analysis, this article evaluates the proposal for a US Blue New Deal — as designed by Senator Elizabeth Warren — that would be applied towards enhancing socioeconomic resiliency, environmental justice, and addressing social inequities. As part of a critical policy analysis evaluating the areas of focus Warren's Blue New Deal presents, environmental justice and sustainability are central to the success of managing, and enhancing the role of, the blue economy. The challenges facing the Blue New Deal reflect a “one size fits all” federal approach that has implications for addressing multifaceted obstacles in key sectors of the blue economy, its governance, and tackling interconnected crises that exacerbate socioeconomic inequities and vulnerabilities of marginalised coastal communities. This article proposes a blue justice framework for the Blue New Deal that seeks to address the tensions and contradictions that exist in its current form and indicates how a comprehensive policy framework can enhance the sustainability and equitable involvement of the blue economy. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG). © 2022 Royal Geographical Society (with the Institute of British Geographers).
3 citations (Crossref) [2023-10-31] tex.coden: GGJOA tex.document_type: Article tex.source: Scopus
Keywords: dept.egm; dept.mgt; dept.soc; peer-reviewed